Marine diatoms as a source of bioactive compounds: bioprospecting and cryopreservation - Madeo, Maria Letizia; Angelone, Tommaso; Cozza, Radiana; Romano, Giovanna (Università della Calabria, 2025)
Diatoms (Bacillariophyceae) are photosynthetic eukaryotic microalgae that play a key role in ecosystems, accounting for 20-25% of global primary production, approximately 40% of annual marine biomass production (Bhattacharjya et al., 2020). One of their most intriguing aspects is their inter- and intraspecific diversity, both morphological and functional. In recent years, this class of microalgae has emerged as an attractive resource for producing high-value compounds due to their ability to synthesize various bioactive substances (proteins, lipids, polyunsaturated fatty acids, vitamins, pigments, etc.), but also to rapidly increase their biomass, and physiologically adapt to diverse growth conditions (Lauritano et al., 2018; de Jesús-Campos et al., 2020; Cutignano et al., 2022). In this context, the aim of this Ph. D project was to investigate the use of novel diatom species for the production of industrially high-value compounds, such as fucoxanthin, while also evaluating various conditions and techniques for their long-term cryopreservation. One of the aims of this work focused on the study for fucoxanthin production in Thalassiosira rotula, abundant species in the Tyrrhenian Sea with high levels of bioactive compounds (prostaglandins, polyunsaturated fatty acids, xanthophylls). To enhance biomass yield and fucoxanthin content in cultures, two different strains of T. rotula were assessed, and various approaches were applied, including the use of preinocula with varying volumes and abiotic treatments (low light intensity and increased nitrate concentration in the culture medium). Furthermore, through an omics approach in collaboration with the Zoological Station “Anton Dohrn” of Naples, several aspects of treated and untreated cultures were analysed, including morphophysiological variations, photosynthetic pigment content, and the modulation of key genes involved in the fucoxanthin biosynthesis pathway. Considering the potential biotechnological applications of T. rotula, and in general of diatoms, another focus of this project was to test cryopreservation methods on different diatom species. In this context, traditional culture maintenance methods are known to present challenges, such as potential loss or alteration of species characteristics over time, genetic mutations leading to physiological changes and reduced biotechnological relevance, and, importantly, contamination due to repeated handling (Godhe & Rynearson, 2017; Bulankova et al., 2021). In light of this, alternative methods such as cryopreservation are becoming increasingly prevalent in algal culture collections (Stock et al., 2018). However, despite experimental efforts in microalgal cryopreservation, no universal protocol exists (Day, 2007; Tanniou et al., 2012; Buhmann et al., 2013; Kumari et al., 2016). This is closely linked to the inter- and intraspecific variability of these organisms and the diverse stress response mechanisms triggered during cryopreservation, which remain poorly understood. Given the high specificity required for successful cryopreservation techniques, this work evaluated and optimized several parameters, such as incubation time in the cryoprotective agent and freezing methods (rapid freezing or slow cooling freezing), across five different diatom species characterized by size, environmental adaptation, biotechnological potential, and cell cycle stage. Part of the research activities focused on cryopreservation techniques was conducted at Ghent University, within the Protistology and Aquatic Ecology (PAE) laboratories and the BCCM Diatom Culture Collection (BCCM/DCG).
UNIVERSITA’ DELLA CALABRIA Dipartimento di Biologia, Ecologia e Scienze della Terra (DiBEST) Dottorato di Ricerca in Life Science and Technology. Ciclo XXXVII
Keywords: diatomee marine; composti bioattivi; crioconservazione; bioprospecting; fucoxantina